56.2k views
1 vote
I need help simplifying #6

I need help simplifying #6-example-1
User Demeshchuk
by
5.0k points

2 Answers

4 votes

Answer:

Therefore,


(24x^(5)y^(9)z^(-8))/(10x^(-3)y^(4)z^(-4))=(12x^(8)y^(5))/(5z^(4))

Explanation:

Simplify


(24x^(5)y^(9)z^(-8))/(10x^(-3)y^(4)z^(-4))

Solution:

Using the Identities


1.\ x^(-a)=(1)/(x^(a))


2.\ (1)/(x^(-a))=x^(a)


3.\ (x^(a))/(x^(b))=x^((a-b))

Therefore,


(24x^(5)y^(9)z^(-8))/(10x^(-3)y^(4)z^(-4))=(24x^((5+3))y^((9-4))z^((-8+4)))/(10)


(24x^(5)y^(9)z^(-8))/(10x^(-3)y^(4)z^(-4))=(2* 12x^(8)y^(5)z^(-4))/(2* 5)


(24x^(5)y^(9)z^(-8))/(10x^(-3)y^(4)z^(-4))=(12x^(8)y^(5))/(5z^(4))

Therefore,


(24x^(5)y^(9)z^(-8))/(10x^(-3)y^(4)z^(-4))=(12x^(8)y^(5))/(5z^(4))

User Legenddaniel
by
5.1k points
2 votes

Answer:

The simplified expression is
(12x^8y^5)/(5z^4)

Therefore
(24x^5y^9z^(-8))/(10x^(-3)y^4z^(-4))=(12x^8y^5)/(5z^4)

Explanation:

Given expression is
(24x^5y^9z^(-8))/(10x^(-3)y^4z^(-4))

To simplify the given expression as below :


(24x^5y^9z^(-8))/(10x^(-3)y^4z^(-4))


=(12x^5y^9z^(-8))/(5x^(-3)y^4z^(-4))


=(12x^5y^9z^(-8)x^3y^(-4)z^4)/(5) ( by using the property
a^(m)=(1)/(a^(-m)) )


=(12x^5.x^3.y^9.y^(-4)z^(-8)z^4)/(5)


=(12)/(5)x^(5+3).y^(9-4).z^(-8+4) ( by using the property
a^m.a^n=a^(m+n) )


=(12)/(5)x^8y^5z^(-4)


=(12x^8y^5)/(5z^4) ( by using the property
a^(-m)=(1)/(a^m) )


(24x^5y^9z^(-8))/(10x^(-3)y^4z^(-4))=(12x^8y^5)/(5z^4)

The simplified expression is
(12x^8y^5)/(5z^4)

Therefore
(24x^5y^9z^(-8))/(10x^(-3)y^4z^(-4))=(12x^8y^5)/(5z^4)

User Meyquel
by
5.0k points